Urban health and the prevalence of non-communicable diseases in Malaysia - Ismail, Normaz Wana; Sivadas, Sudha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Urbanisation is a key determinant of population health. Malaysia’s exemplary economic growth in the early 1990s and the consequent development and urbanisation led to significant changes in health, lifestyle and quality of life. Rising expectations, changing demographics and nutrition and disease transitions were challenges synonymous to an increasingly urban Malaysia. As the Government targets optimal population health, this paper aims to explore one of the many challenges of urbanisation, namely the prevalence of non-communicable diseases or NCDs. For the purpose of this paper, NCD is proxied by Diabetes Mellitus. Methods: This study is based the 2015 National Health and Morbidity Survey, which is a cross-sectional population-based survey, involving 30,000 respondents. Given the binomial nature of the survey variables, the multinomial Probit model was employed using the STATA statistical software. Results: Generally, age, gender and race are significant in determining health outcomes. Socioeconomically, all three variables of income, education and employment are significant. For lifestyle factors, findings show that only the weight and physically active status have a role in determining health outcomes. Finally, the urban variable is also positive and significant. Conclusion: Findings show that the prevalence of Diabetes Mellitus, is rising along with urbanisation and that there is a health penalty for the urban population and also for those who do not embrace healthy lifestyles. Additionally, other factors are equally important as urban health determinants, encompassing both the demographic and socioeconomic factors.